Ferroic properties of 0.675[Pb(Mg1/3Nb2/3)O3]−0.325[PbTiO3]/CoFe2O4 prepared by spark plasma sintering. Issue 174 (1st September 2016) - Viana, D. S. F.; Milton, F. P.; Jimenez, K. R. C. P.; Gualdi, A. J.; Camargo, P. C.; de Oliveira, A. J. A.; Eiras, J. A.; Bhalla, A.; Guo, R.; Garcia, D.
ABSTRACT: This paper reports the electric, magnetic and magnetoelectric properties of particulate composites of the system with ferroelectric phase 0.675[Pb(Mg1/3 Nb2/3 )O3 ]−0.325[PbTiO3 ] and magnetic phase CoFe2 O4 prepared by Spark Plasma Sintering technique. Optimized sintering and thermal annealing parameters were applied in order to achieve highly dense microstructure with sub micrometric grain size distribution for both phases. The results from the dielectric measurements showed a diffuse and dispersive phase transition. P-E and M-H loops revealed the simultaneous existence of ferroelectric and ferrimagnetic ordering, respectively. Moreover, at cryogenic temperatures an anomalous behavior on the bias magnetic field dependence was observed for the magnetoelectric voltage coefficient.